Impacts of winter grazing on soil health in southeastern cropping systems. Issue 2 (13th April 2022) - Crowell, Hayley; Gamble, Audrey V.; Feng, Yucheng; Balkcom, Kipling; Yang, Anna
Abstract: Coastal Plain soils are often characterized by low soil organic carbon (SOC) as a result of natural and anthropogenic factors. A rotation of cotton ( Gossypium hirsutum L.) and peanut ( Arachis hypogaea L.) under conventional tillage is typical in this region, but an opportunity to increase SOC and improve soil health by incorporating winter grazing of cover crops exists for producers with row crop and livestock operations. A study to assess winter grazing impacts on soil health was established in the U.S. Coastal Plain. Three cattle removal dates and an ungrazed control were evaluated for impacts on selected soil health indicators: SOC, permanganate oxidizable carbon (POXC), water stable aggregates (WSA), penetration resistance (PR), microbial biomass C (MBC), and arbuscular mycorrhizal fungi (AMF) colonization rates. After two years, MBC was highest in the control treatments, likely due to greater cover crop biomass on the soil surface at termination. No differences were observed between treatments for SOC, POXC, WSA, PR, or AMF. Increased cotton lint yield was observed in control and mid‐February treatments in 2019, likely due to greater cover crop residues on the soil surface following grazing, which may have conserved soil moisture during the growing season. Peanut yields were unaffected by treatments in 2020. Lack of differences in soil health indicators suggests that integrating winter‐grazing livestock does not negatively nor positively impact selected dynamic soil properties in the short‐term, but more time under grazing treatments is needed to thoroughly evaluate how winter‐grazing livestock impacts soil health and crop yield. Core Ideas: Physical and chemical soil health indicators were unaffected by grazing period. Microbial biomass C was greatest in an ungrazed control treatment. Cotton lint yield was improved for ungrazed and shorter grazing periods after a year.